HUBUNGAN PELAYANAN KEPERAWATAN DENGAN KEPUASAN PASIEN DI PUSKESMAS TORUE KABUPATEN PARIGI MOUTONG - Freny Ravika Mbaloto; Ni Ketut Elmiyanti; I Nyoman Triagus Jatiasa (Sekolah Tinggi Ilmu Kesehatan Indonesia Jaya Palu, 2023)
Patient satisfaction is an integral part of the mission and goals of the nursing profession because the increasing intensity of global and domestic competencies will improve quality nursing services. The results of the preliminary survey at the Torue Health Center showed that patients were dissatisfied with nursing services because nurses lacked a smile and greeted patients when they met, and it was difficult to find or contact them when needed. The purpose of this study was to determine the relationship between nursing services and patient satisfaction at the Torue Community Health Center, Parigi Moutong Regency.This type of research is analytic (cross sectional). The research variables are nursing services (independent variable) and patient satisfaction (dependent variable). The data used are primary and secondary data. Data analysis used univariate and bivariate analysis with Pearson chi-square test). The study population was all inpatients at the Torue Health Center at the time of the study. A sample of 43 patients was taken by accidental sampling. The results showed that from the statistical test results with chi-square (pearson chi-square) it was found that p value = 0.001 which is less than 0.05. This means that there is a relationship between nursing services and patient satisfaction at the Torue Health Center, Parigi Moutong Regency. The conclusion of the study is that there is a relationship between nursing services and patient satisfaction at the Torue Health Center, Parigi Moutong Regency. Research suggestions are expected for the Torue Health Center to be able to further improve the quality of health services so as to increase patient satisfaction undergoing hospitalization